2016
DOI: 10.4274/tod.95914
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Hand Grip Strength with Bone Mineral Density and Vitamin D in Postmenopausal Women

Abstract: Amaç: Bu çalışmanın amacı postmenopozal kadınlarda el kavrama gücünün (EKG) kemik mineral yoğunluğu (KMY) ve D vitamin seviyeleri ile ilişkisini değerlendirmektir. Gereç ve Yöntem: Çalışmaya 131 postmenopozal kadın alındı. EKG Jamar el dinamometresi ile ölçüldü. KMY dual enerji X-ray absorbsiyometri ile lomber omurga ve femur boyun bölgelerinden ölçüldü. Serum 25-hidroksivitamin D (25OHD) seviyeleri tespit edildi. Bulgular: Hastaların yaş ortalaması 61,2±9,2 yıl idi. Ortalama EKG 22,9 kg idi ve 32 hasta (%24,4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Previous research has identified the association of balance impairment with low BMD among postmenopausal women. 42,66 Recently, Mehta and colleagues established a high reliability for the timed up-and-go test to assess functional balance among patients with DRF (with a mean age of 62.6 [SD 7.6] y). 60 This is likely a more feasible test for clinical implementation than the Biodex data we used for our research purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has identified the association of balance impairment with low BMD among postmenopausal women. 42,66 Recently, Mehta and colleagues established a high reliability for the timed up-and-go test to assess functional balance among patients with DRF (with a mean age of 62.6 [SD 7.6] y). 60 This is likely a more feasible test for clinical implementation than the Biodex data we used for our research purposes.…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to the fact that older population were prone to have fracture at low BMD-prone area such as the hip, proximal humerus, and vertebrae 87. According to Serdaroğlu Beyazal et al, HGS test score was significantly correlated with BMD, as postmenopausal women with osteoporosis had a lower HGS test score than postmenopausal women with normal BMD 88…”
Section: Discussionmentioning
confidence: 99%